2013
DOI: 10.1371/journal.pone.0065488
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for CXCR6+ and CXCR6− CD4+ T Cells in the Pathogenesis of Chronic Colitis

Abstract: CD4+ T cells play a central role in the development of inflammatory bowel disease (IBD) via high-level production of effector cytokines such as IFN-γ and TNF-α. To better characterize the colitogenic CD4+ T cells, we examined their expression of CXCR6, a chemokine receptor that is expressed by T cells upon activation and is upregulated in several inflammatory diseases. We found that 80% of colonic lamina propria CD4+ T cells expressed CXCR6 in the CD45RBhigh T cell-transferred colitis model. CXCR6 expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…Relatedness is suggested also for IL17/IFNγ DP cells that emerge in an IL-23-dependent fashion in murine inflammatory bowel disease (55). In a T cell transfer model of chronic colitis, pathogenic CD4 cells marked by CXCR6 include IL-17/IFNγ DP cells along with predominant IL-17 SP and IFNγ SP cells (56); poor proliferation characterizes these cells and thus distinguishes them from the rapidly proliferating CXCR6 + TH cells in EAE. Lastly, encephalitogenic CXCR6 + TH cells have at least one feature, cytotoxic granules, in common with CD4 + cytolytic T cells (CD4 + CTL) that provide, e.g., antiviral protection.…”
Section: Discussionmentioning
confidence: 94%
“…Relatedness is suggested also for IL17/IFNγ DP cells that emerge in an IL-23-dependent fashion in murine inflammatory bowel disease (55). In a T cell transfer model of chronic colitis, pathogenic CD4 cells marked by CXCR6 include IL-17/IFNγ DP cells along with predominant IL-17 SP and IFNγ SP cells (56); poor proliferation characterizes these cells and thus distinguishes them from the rapidly proliferating CXCR6 + TH cells in EAE. Lastly, encephalitogenic CXCR6 + TH cells have at least one feature, cytotoxic granules, in common with CD4 + cytolytic T cells (CD4 + CTL) that provide, e.g., antiviral protection.…”
Section: Discussionmentioning
confidence: 94%
“…The CXCL16 gene is located within the Idd4 T1D risk locus in mouse (27), and CXCR6 is located within the IDDM22 T1D disease locus in man, making this chemokine-receptor pair of strong potential interest (28). This pathway also interested us since CXCR6 has been shown to have a role for trafficking of pathogenic T cells in other animal models of autoimmunity such as EAE and colitis (4244). CXCL16 has also been shown to be elevated in EAE and during rejection of a transplant (42, 4547).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that on CD4 ϩ T cells, CXCR6 serves as an extralymphoid homing receptor (54), and limited studies in humans suggest that it is expressed mainly by memory T cells, particularly T cells in tissues such as lung and at sites of inflammation and cancer (55)(56)(57), although expression on naive cells has been reported as well (58). Studies of CXCR6 expression on nonhuman primate natural host cells have been hindered by a lack of cross-reactivity of anti-human CXCR6 antibodies.…”
Section: Discussionmentioning
confidence: 99%